DINAMIKA HEGEMONI PENGUASAAN HUTAN DI INDONESIA - Rahmat Budiono; Bramasto Nugroho; Hardjanto Hardjanto; Dodik Ridho Nurrochmat (Jurnal Analisis Kebijakan Kehutanan, 2018)
Hegemony means as a victory for the dominant group that is controlled by the mechanism of consensus (consent).  This article attempts to understand the dynamics of state and community relationships regarding the political dynamics of the mastery of forest resources from the feudalism era to the post-colonial era. This research was carried out by using the qualitative analytic approach with literature research method. The results of the study showed that during colonial era, the state hegemony over forests was mainly to maintain its domain against the forest, and it correlates with the use of alliance between the colonial state and local rulers. In the perspective of Gramscian, the existing national political law over the forest is much influenced by the Indonesian organic intellectuals who inherited the ideology of Domainverklaring. The present social forestry program is not actually a counter-hegemonic (victory) of society over state hegemony in forest areas that has been taken place since colonial times, but rather to reinforce state hegemony over forests. To avoid it from triggering a humanitarian crisis, the solution then will depend on the country's ability to uphold justice in forest resources management.